Walkeromya plumipes (Philippi) (Diptera: Bombyliidae), a parasitoid associated with carpenter bees (Hymenoptera: Apidae: Xylocopini) in Argentina - Ávalos-Hernández, Omar; Lucia, Mariano; Álvarez, Leopoldo J.; Abrahamovich, Alberto H. (Zootaxa, 2011)
This is the first record of the association between Walkeromya plumipes (Philippi) (Diptera: Bombyliidae) and Xylocopa Latreille (Hymenoptera: Apidae) in Argentina. The pupal development and morphology of Walkeromya plumipes, a parasitoid of Xylocopa splendidula Lepeletier, are described. A parasitized nest was collected from Santiago del Estero province, Argentina. The development of the bombyliid fly and large carpenter bees in the nest were observed in the laboratory for a period of 28 days. A detailed description of the fly adult and pupal stages were carried out. This is the first record of W. plumipes parasitizing X. splendidula. This is also the first complete description of this fly species, including male genitalia. With the data presented here the geographical distribution of the parasite is expanded. The results suggest a close relation between the parasitoid and its host, as the genus Walkeromya Paranov has been found parasitizing only carpenter bees of genus Xylocopa.